Stability and morphology-dependence of Sc3+ ions incorporation and substitution kinetics within ZnO host lattice. (November 2015) - Yumak, Ayşe; Turgut, Güven; Kamoun, Olfa; Ozisik, Haci; Deligoz, Engin; Petkova, Petya; Mimouni, Refka; Boubaker, Karem; Amlouk, Mosbah; Goumri-Said, Souraya
Abstract: In this study, sol–gel spin coating route was carried out to prepare Scandium doped ZnO thin films with different controlled percentage (1–7%). Particularly, it has been demonstrated, through original conjoint morphological-structural and optical investigations, that some interesting physical properties were induced. Indeed, X-ray diffraction (XRD) analysis shows that (002) preferential crystalline plane for Sc doped ZnO films was kept along with ZnO hexagonal würtzite structure, although Sc doping seemed to cause a decrease in crystallinity. Except for 1 at% Sc doping ratio, optical band gap changes reversely with Urbach energy with a decrease in optical gap and a broadening of the absorption tail. Ab-initio calculations of lattice dynamical properties outlined additional strong hybridization between Sc and O atoms and show the stability of Scandium doped ZnO.